COORDINATE EXPRESSION OF CYTOKERATIN-7 AND CYTOKERATIN-20 DEFINES UNIQUE SUBSETS OF CARCINOMAS - Wang, N. P.; Zee, S.; Zarbo, R. J.; Bacchi, C. E.; Gown, A. M. (Lippincott-raven Publ, 1995)
We tested the hypothesis that the coordinate expression of cytokeratin 7 (CK 7) and cytokeratin 20 (CK 20) could distinguish among carcinomas arising from different primary sites. A total of 384 cases of carcinomas primary to various organs, as well as 16 cases of malignant mesothelioma, were evaluated using commercially available monoclonal antibodies and an avidin-biotin immunoperoxidase technique. The subset of tumors strongly expressing both CK 7 and CK 20 included virtually all bladder transitional cell carcinomas and the majority of pancreatic adenocarcinomas; the tumors negative for both CK 7 and CK 20 were largely restricted to hepatocellular, prostate, and renal cell carcinomas in addition to squamous cell and neuroendocrine carcinomas of lung. The CK 7-/CK 20+ immunophenotype, however, was highly characteristic of adenocarcinomas of colorectal origin, whereas CK 7+/CK 20- immunophenotype was typically seen in the vast majority of carcinomas arising from other sites, including ovary, endometrium, breast, and lung, as well as malignant mesothelioma. Gastric carcinomas were the most heterogeneous subgroup with respect to CK 7/CK 20 immunophenotype. In the subset of mucinous tumors, striking immunophenotypic differences were noted among those primary to the breast (CK 7+/CK 20-), gastrointestinal tract (CK 7-/CK 20+), and ovary (CK 7+/CK 20+). In all cases investigated, this CK immunophenotype was invariant in metastatic vs. primary tumors. It is concluded that, in the appropriate clinical setting, the CK 7/CK 20 immunophenotype of carcinomas is a valuable diagnostic marker in the determination of primary site of origin.
Keywords: CYTOKERATINS; CK 7; CK 20; PROTEIN IT; IMMUNOHISTOCHEMISTRY